Penyuluhan Hukum: Kajian Yuridis tentang Rancangan Qanun Nikah Siri Provinsi Aceh, Pembenahan, dan Dampak pada Masyarakat di Sekolah Tinggi Ilmu Tarbiyah Aceh Simeulue - Wolly Mistiar; Afriani; A’zizah; Adi Saleh; Suhaidi; Mohd. Eka Putra; Syarifuddin Hasyim (Yayasan Kawanad, 2023)
The proposed Qanun on polygamy by the Acehnese elite (executive and legislative) is aimed at the wider community because of the widespread phenomenon of unregistered marriages. Siri marriage is not prohibited in Aceh in fact the administrative requirements are relaxed for ordinary people. This gap raises the question of whether the Acehnese elite proposed the polygamy qanun for the benefit of society or for subjective interests. This article is classified as field research with a qualitative approach. The methodology used is descriptive-analytical research. The results of the research found that the reactor for the implementation or key factor of family law qanun in Aceh lies in the condition where polygyny requirements are tightened beyond the provisions of the Compilation of Islamic Law (KHI) and the requirements for Siri Marriage which are relaxed. based on KHI provisions. The motive was the Acehnese elite's efforts to have their unregistered wives recognized (legality) in Aceh's polygyny qanun. These findings can be input for family law studies to create more objective and independent regulations, especially in regions that have special autonomy rights.